Training experience and maturational, morphological, and fitness attributes as individual performance predictors in male and female under-14 Portuguese elite basketball players - Ramos, S.; Volossovitch, A.; Ferreira, A. P.; Fragoso, I.; Massuça, L. M. (The Journal of Strength and Conditioning Research, 2021)
The association of the biological maturation, morphological attributes, and fitness attributes of 13- to 14-year-old players selected to regional basketball teams, which participated in the Portuguese Festival of Youth Basketball, was analyzed in the study. A total of 416 under-14 Portuguese elite basketball players (male, n = 224; female, n = 192) were evaluated in this cross-sectional study. Maturational parameters (maturity offset and predicted age at peak height velocity), morphological attributes (body mass, stature, skinfolds, and lengths), and fitness (sprint, agility, jump, and upper-body strength) attributes were measured. In addition, basketball game performance was assessed using technical statistics (rebounds and point averages) and the performance index rating (PIR). Correlation analyses indicated that male players with better PIR/minute were taller, had a longer hand span, had more free-fat mass, and demonstrated better results in all jumping tests, upper-body strength tests, 20-m speed test, and agility T-test. Female players with better PIR/minute were significantly older, more matured, heavier, taller, and had longer arm and hand span. They also demonstrated better results in jumping tests, medicine ball throw, had greater practice experience, and were subjected to higher training loads. Multiple regression analysis showed that combined stature, handgrip strength, agility, and countermovement jump (with arm swing power) can be considered strong predictors of PIR per time played for male players. The prediction model for female players indicated that maturity offset, practice experience, and agility were the strongest predictors of basketball performance. In conclusion, the results of this study indicate that around puberty, physical fitness attributes of elite basketball players of both sexes are associated with game performance parameters. Two regression models have been estimated to predict the performance of youth basketball players of both genders.